KEBIJAKAN PAJAK DALAM APBN: KOMPLEKSITAS KEPENTINGAN NEGARA, PENGUSAHA DAN KEADILAN MASYARAKAT - Suhud Alynudin Suhud Alynudin (NIAGARA Scientific Journal, 2016)
Tax is one of the main components in the state budget. In addition to state interests, tax policy touches on various interests, especially entrepreneurs and the public. The tug-of-war between related parties has caused tax policy to become an important issue in APBN discussions. Bringing together all interests is a solution that will be accepted by the relevant parties.